Faktor-Faktor Yang Berpengaruh terhadap Tingkat Pengguliran Dana Bank Syariah - Emile Satia Darma; Rita Rita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2011)
The purpose of this research is to find out the factors affecting the financing level of sharia banks. This research uses monthly financial reports Islamic Commercial Bank Foreign Exchange 2006-2009 period as the object of research. To analyze the data used multiple linear regression method. The result showed that all the variables, namely exchange rate, inflation, third party funds (DPK), Sertifikat Wadiah Bank Indonesia (SWBI) and bank income jointly affect the financing level of sharia banks. The five variables capable of explaining the dependent variable was 31.2% and the remaining 68.8% is explained by other variables outside the research model. Partially, exchange rates (significantly negative), inflation (positive is insignificant), third party funds (positive is insignificant), SWBI (significantly negative) and the income of the bank (negative not significant) to the level of scrolling funds of Islamic banks.